Japan’s Strategy on Managing Territorial Disputes of Senkaku Islands - Essa Rahmadhani Dirha Kirana; Rafyoga Jehan Pratama Irsadanar (Journal of Islamic World and Politics, 2022)
The purpose of this study is to clarify and provide new information regarding the Japanese approach to handling territorial issues involving the Senkaku Islands. By applying the Negotiation and Mediation theory by Dean G. Pruitt and Peter J. Carnevale to evaluate and further explain the types of negotiations between Japan and China to resolve the territorial issues of the Senkaku Islands, it will explain the process of Japan's strategy for doing so. The study discovered that both countries went through several dynamics in their negotiating process using the Negotiation and Mediation theory. To identify the best way to develop a solution, Japan and China used two strategies: the first was the contesting strategy, which took place at the start of the negotiating process, and the second was the yielding or concession strategy. Finally, carry out the problem-solving plan whereby both parties agreed to host a Joint Development to put an end to the territorial disputes over the Senkaku Islands.